Implementation of Activity Based Costing (ABC) for Rub Oil Products at UD. Making Oil Rub Hero Samarinda - Nuuridha Matiin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The emergence of the concept of ABC (Activity Based Costing) because the ABT (Traditional Cost Activity) system does not connect supporting activities with the products produced. The purpose of this study is to find out the application of Activity Based Costing (ABC) to UD. Hero Rub Oil. Data collection methods use observations, interviews, and documentation. Data analysis techniques use the Activity Based Costing (ABC) method on UD. Hero Rub Oil. The results of calculations using the Activity Based Costing (ABC) method obtained for the processing and packing of oil for 1 ml are Rp 2,891.43 / bottle on UD. Hero Rub Oil.